Comments on qualitative results for investment proportions - Roll, Richard; Ross, Stephen A. (Journal of Financial Economics, 1977)
Some mean/variance efficient portfolios will have positive investments in all individual assets when covariances satisfy the conditions given here. These conditions are more useful empirically than qualitative results that depend on the inverse covariance matrix. The prospect appears dim for general and useful qualitative results.